Sulfur dots and iron co-doped nickel-based metal-organic frameworks with high nanozyme activity for the colorimetric determination of α-glucosidase activity - Zhang, Hanqiang; Luo, Jianfei; Gan, Feng (Analytica chimica acta, 2023)
Alpha-glucosidase (α-Glu) plays a crucial role in regulating the normal physiological function of the body; therefore, α-Glu activity detection is crucial in clinical studies. In this study, a nickel-based metal-organic framework (Ni-MOF) co-doped with sulfur dots (SDs) and iron (Fe) was designed and constructed for the colorimetric detection of α-Glu. The SDs/Fe/Ni-MOF shows a very low Michaelis–Menten constant (0.0466 mM) for H2O2, suggesting a very high affinity for H2O2. Additionally, the free radicals generated by the nanozyme-catalyzed reaction were analyzed, and the feasibility of the nanozyme-catalyzed process was further verified using density functional theory. The bimetallic (Fe and Ni) can improve the catalytic activity of the material, and sulfur can improve the affinity with the substrate to further enhance the catalytic performance. Notably, hydroquinone (HQ) inhibits nanozyme activity, whereas α-Glu hydrolyzes alpha-arbutin (α-Arb) and subsequently produces HQ. Therefore, this study developed a method for detecting α-Glu activity using α-Arb as a substrate. This method has high selectivity, a wide detection range (1.00–100 U L−1), and a low detection limit (0.525 U L−1). Finally, the method was used to α-Glu activity detected in serum samples with good accuracy. This study provides a new method for the detection of α-Glu. [Display omitted] •SDs and Fe co-doped Ni-MOF was synthesized by hydrothermal method.•The SDs/Fe/Ni-MOF has high nanozyme activity.•The Michaelis-Menten constant for H2O2 was as low as 0.0466 mM.•The nanozyme catalytic process was studied by theoretical calculations and experiments.•This method was used for the colorimetric detection of α-Glu activity in serum.